Un giro editorial en la visión ideológica de América Latina: La «Colección América Nuestra» de la Editorial Universitaria (Santiago,1955-1961) - González Inostroza, Mario Andrés (2025)
The following article addresses the Colección América Nuestra, directed by the Chilean socialist activist Clodomiro Almeyda between 1955 and 1961. It is argued that the Editorial Universitaria, with this new series, opened itself to a new ideological market, seeking to provide a panorama of the Latin American situation that would rescue a national and anti-imperialist project. Based on the analysis of the set of books in the series, the publisher’s documents, the editor’s ideas and media reviews, the specific context in which the works circulated and their reception are established.